Comparison of preoperative anxiety in reconstructive and cosmetic surgery patients - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Surgery is a serious stressor and a cause of anxiety for the patients. Reconstructive surgery patients are mostly operated on because of certain functional impairment or disability; on the contrary, cosmetic surgery patients do not have any physical impairment and they are operated on because of mostly psychologic reasons. The aim of this study was to compare the anxiety levels in the reconstructive surgery patients and cosmetic surgery patients preoperatively. Thirty-two patients in the reconstructive surgery group and 30 patients in the cosmetic surgery group were included in the study. State Trait Anxiety Inventory was used to measure the anxiety levels in these 2 groups preoperatively. The 2 groups were similar in characteristics such as age, gender distribution, number of previous operations, and trait anxiety scores. Mean state anxiety scores obtained for the reconstructive surgery group was 38.0 +/- 8.7, while it was 44.2 +/- 10.79 for the cosmetic surgery group (t test, degrees of freedom = 60, P = 0.015). This study reveals that preoperative anxiety levels in the cosmetic surgery patients are higher than those of the reconstructive surgery patients. Therefore, adequate preoperative preparation for cosmetic surgery should include attempts to cope with anxiety. Anxiolytics may be used more liberally and professional psychologic assistance may be required.
Keywords: preoperative anxiety; cosmetic surgery; reconstructive surgery; PLASTIC-SURGERY; MUSIC; OUTCOMES